2021
DOI: 10.1016/s1473-3099(20)30474-6
|View full text |Cite
|
Sign up to set email alerts
|

Validating clinical practice guidelines for the management of children with non-blanching rashes in the UK (PiC): a prospective, multicentre cohort study

Abstract: Validating clinical practice guidelines for the management of children with nonblanching rashes in the United Kingdom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…Petechiae have been more commonly reported among MenB infections and less commonly among serogroups Y and W [4, 14]. A recent study from the UK, where meningococcal MenB and MenC vaccination is implemented, found IMD now to be a rare cause of petechiae in children presenting with fever [22].…”
Section: Discussionmentioning
confidence: 99%
“…Petechiae have been more commonly reported among MenB infections and less commonly among serogroups Y and W [4, 14]. A recent study from the UK, where meningococcal MenB and MenC vaccination is implemented, found IMD now to be a rare cause of petechiae in children presenting with fever [22].…”
Section: Discussionmentioning
confidence: 99%
“…When modern scientists compare the physical characteristics of children with HSP to those of healthy children, they discover that children with HSP have the largest percentage of yin deficit, indicating that children with partial yin deficiency are more prone to HSP [ 12 ]. According to literature [ 13 ], the percentage of HSP children with a balanced TCM constitution was 36.94 percent, 33.78 percent had a partial yin deficit, and 53.57 percent had a partial yin deficiency, and the second was Qi insufficiency.…”
Section: Related Workmentioning
confidence: 99%
“…5 21 The findings of the parent study from which the data in this analysis are drawn (the PiC study) further support this, demonstrating that an abnormal WCC, neutrophil count or elevated CRP were all poorly specific for MD (0.67, 029 and 0.73), respectively. 22 These specificities were significantly lower than that of the LAMP test (specificity 0.97, p<0.0001).…”
Section: Discussionmentioning
confidence: 83%